Retaining Talent: The Role of the Personal and Contextual Factors - Talat Islam; , Zeshan Ahmer; Naeem Mushtaq (The Lahore Journal of Business)
Earlier studies have focused on the attitudinal and behavioral aspects of employee turnover. However, this study empirically investigates the contextual (i.e. job complexity, developmental feedback and perceived organizational support) and personal (i.e. proactive personality and core self-evaluations) aspects in order to elucidate turnover intention among the private sector universities of Pakistan. The study used a questionnaire-based survey that was circulated amongst the faculty members of the private universities, and 758 responses were used for the final data analysis. Moreover, the structural equation modeling was applied and revealed that core self-evaluation, developmental feedback, job complexity and perceived organizational support are negatively associated with turnover intention. However, the element of proactive personality was found to have a nonsignificant association with turnover intention. This study has theoretical and practical implications for universities and recruitment departments.